Accumulation of progressing deformations of the threaded joints M16 under low cyclic bending/Progresuojantis deformacijų kaupimasis mažaciklio lenkimo veikiamose srieginėse jungtyse M16 - Leonavičius, Mindaugas; Krenevičius, Algimantas; Šukšta, Marijonas (Journal of Civil Engineering and Management, 1998)
In some threaded joints, over a period of operation the conditions of compression are created, most likely owing to the prestress and bending caused by external loads. For elements in the cross-section in which the stresses are distributed unevenly, some standards approve using the exceeding of nominal values of yield limit short-cyclic longevity. The greater part of experiments is carried out under the influence of axial cyclic load on a joint, and the smaller part of experiments is carried out under the action of stretching and bending. The presented data show the fatigue proccess within the elements the working conditions of which depend on the influence of other elements. Results of the laboratory failure tests of the threaded joints produced from steel 25XIMΦ are used as a basis for investigation into of the stud-bolt M16. A static and kinematic theorem is used for the analysis of stress state of stud-bolt the initiation; propagation of fatigue cracks in the threaded joints is taken into account. The increase of prestress and variable repeated loading of stud-bolt lead to the plastic deformation of certain zones of bolts. Due to such non-elastic deformation dangerous states may occur leading to deterioration of bolts. In terms of the theory of shakedown, the analysis of experimentally tested threaded joints has been carried out in order to evaluate their stability in the process of cyclic load and also to evaluate a boundary state, where plastic deformations can be accumulated. The theory of static and kinematic shakedown provides the possibility to determine boundary states, ie the flowing of variable sign and accumulation of one-sided deformation. The conditions of shakedown are changed by the development of cracks. By means of obtained analytical expressions one can evaluate the conditions of changing variable flow and propagating form of crack at any depth from its appearance to its critical size. According to the produced conditions of shakedown with one-sided and two-sided crack (the relation of crack depth to cross-section radius is 0; 0.1; 0.2) the state of threaded joints is present on the diagram. Using the radius slope of similar cycles, one can calculate the safety factor of shakedown. A summarized and produced by testing safety factor is of value from 1.02 to 1.8. The investigation of threaded joints loosening mechanisms show that this process depends on the prestress, cyclic loading, crack propagations and accumulation of increasing deformations. The threaded joints adapt to circumstances. Article in Lithuanian. First Published Online: 26 Jul 2012